IoT Adoption in Botswana's SMEs: Technological Readiness and Government Initiatives - Mphale, Ofaletse; Gorejena, Karikoga Norman; Nojila, Olebogeng Hellen (Universitas Bina Darma, 2024)
As Botswana seeks a more diversified and developed economy, fostering a robust Small and Medium-sized Enterprises (SME) sector is paramount. Consequently, integrating Industry 4.0 technologies, particularly the Internet of Things (IoT), presents a promising possibility for stimulating SME growth. Nonetheless, successful IoT adoption hinges on understanding Botswana's technological landscape. This study employed a Systematic Reviews and Meta-Analyses (PRISMA) guideline to survey the existing literature (academic and grey literature) published between 2015 and 2024 on Botswana's digital readiness. The review examined several areas of technological readiness, including e-commerce legislation, Information and Communication Technology (ICT) education, infrastructure investment, government online services, e-participation initiatives, internet costs, policy framework, cybercrime threats, and overall technology adoption. Results showed that while Botswana has made progress in digital integration, its digital maturity is still evolving. Strengths were found in areas including; e-commerce legislation, ICT education and infrastructure investment. However, weaknesses persist in areas including; limited government online services, limited e-participation initiatives, high internet subscription costs, inadequate policy framework, cybercrime threats, infrastructure limitations, and overall low technology adoption. These findings will equip SME decision-makers and policy makers with valuable insights to assess their digital preparedness for IoT adoption, while also considering Botswana's digital environment.